Bangladesh insulin guideline (premix) for type 2 diabetes - Mahtab, H; Latif, ZA; Pathan, F; Mollah, AS; Siddiqui, NI; Khan, LA; Mannan, MA; Ahmed, T; Uddin, F; Ashrafuzzaman, SM (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):173-182 The abstract of this article is available on the PubMed website